Public perception of the use of digital contact-tracing tools after the COVID-19 lockdown: sentiment analysis and opinion mining - Huang, Zhilian (2022)
Singapore's national digital contact-tracing (DCT) tool-TraceTogether-attained an above 70% uptake by December 2020 after a slew of measures. Sentiment analysis can help policymakers to assess public sentiments on the implementation of new policy measures in a short time, but there is a paucity of sentiment analysis studies on the usage of DCT tools.